Introducing Thermal Inertia for Monitoring Snowmelt Processes With Remote Sensing. Issue 8 (24th April 2019) - Colombo, R.; Garzonio, R.; Di Mauro, B.; Dumont, M.; Tuzet, F.; Cogliati, S.; Pozzi, G.; Maltese, A.; Cremonese, E.
Abstract: Thermal inertia has been successfully used in remote sensing applications that span from geology, geomorphology to hydrology. In this paper, we propose the use of thermal inertia for describing snow dynamics. Two different formulations of thermal inertia were tested using experimental and simulated data related to snowpack dynamics. Experimental data were acquired between 2012 and 2017 from an automatic weather station located in the western Italian Alps at 2, 160 m. Simulations were obtained using the one‐dimensional multilayer Crocus model. Results provided evidences that snowmelt phases can be recognized, and average snowpack density can be estimated reasonably well from thermal inertia observations ( R 2 = 0.71; RMSE = 65 kg/m 3 ). The empirical model was also validated with manual snow density measurements ( R 2 = 0.80; RMSE = 54 kg/m 3 ). This study is the first attempt at the exploitation of thermal inertia for snow monitoring, combining optical and thermal remote sensing data. Plain Language Summary: Alpine snow represents a fundamental reservoir of fresh water at midlatitude. Remote sensing offers the opportunity to estimate snow properties in different spectral domains. In particular, the knowledge of the spatial and temporal variability of snow density could allow modeling of the snow water equivalent, which knowledge is crucial for managing water resources in the face of current climate change. In this study we show for the first time that snow thermal inertia can contribute to monitoring of snowmelt processes and snow density, opening new perspectives for remote sensing of the cryosphere. Key Points: Snow thermal inertia resembles the different phases of snowmelt processes An empirical model is proposed for estimating snow density from apparent thermal inertia This study may open new perspectives in remote sensing of snowmelt processes